Effect of nano-silica on chemical and volume shrinkage of cement-based composites. (30th June 2020) - Wang, Jinbang; Cheng, Yong; Yuan, Lianwang; Xu, Dongyu; Du, Peng; Hou, Pengkun; Zhou, Zonghui; Cheng, Xin; Liu, Shuai; Wang, Yuguang
Highlights: Nano-silica aggravated the chemical shrinkage of cement paste. Nano-silica increased the volume shrinkage of cement concrete. The action mechanism of nano-silica on chemical shrinkage was discussed. The acceleration hydration effects of nano-silica plays leading role in chemical shrinkage. Abstract: Nano-materials modified cement-based materials have attracted wide attention due to their advantages of improving early strength and durability. However, few studies have been conducted on influence of nano-materials on chemical shrinkage of paste and volume shrinkage of concrete. Therein, the influence rules of nano-silica on chemical shrinkage of paste and volume shrinkage of concrete and its action mechanism have been explored and discussed. The result indicated that added nano-silica aggravated the chemical shrinkage of paste and volume shrinkage of the concrete. The paste chemical shrinkage and concrete volume shrinkage increased with the amount of nano-silica in particular as presented in early stage. The chemical shrinkage of cement at 3d and 28d increased by 93.7% and 57.5% respectively, when adding 1.2% nano-silica. Correspondingly, the 1d, 7d and 60d volume shrinkage of concrete increased by 82.1%, 66.7% and 16.7% respectively. The action mechanism of shrinkage intensification is mainly the pozzolanic effect, nucleation effect and acceleration hydration effect of nano-silica, which accelerated the cement hydration.